Relationship between parenting styles, assertiveness and attitudes towards seeking professional psychological help among university students - Tang, Lee Xien; Zakaria, Noor Syamilah (UiTM Press, 2022)
Professional psychological help exists to assist a society in dealing with issues in daily life. However, the willingness of a society to accept these services is a concern that contributes to the effectiveness of the said services. The attitude of society towards these services reflects its personal values, and it is often based on personal experiences with its surroundings, such as family environments. The attitude mentioned also reflects assertiveness of people in interactions that may result in a different level of openness in accepting psychological help for handling personal issues. The purpose of this correlational study is to determine the relationships that may exist between parenting styles, assertiveness and attitudes towards seeking professional psychological help among university students. A total number of 303 respondents were involved in this study. Instruments used in the study include the Parental Authority Questionnaire (PAQ), the Assertion Inventory, as well as the Attitudes towards Seeking Professional Psychological Help Scale (ATSPPHS). The study has found that there is negligible relationship between parenting styles and attitudes towards seeking professional psychological help; however, the authoritarian parenting style has a significant impact on attitudes towards seeking professional psychological help. There is a significant relationship between assertiveness level and attitude towards seeking professional psychological help. This study implies that counsellors may need to take into consideration parenting styles and the assertiveness of their clients in promoting counselling services to build more positive attitudes towards the services rendered.